(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
With less than 2% of new renewable energy production, Switzerland is a poor performer in international comparison. A study carried out for the Swiss Federal Office of Energy showed constraints explaining this low number. One of these is a need for companies to optimize their sales process. GROUP-IT has responded to these needs by developing an approach of grouped tendering of solar panel installations. This article looks at how solar panel installation companies are improving their pricing strategy over time, and how to measure this evolution. In this study, we worked in two steps. A first grouped tendering collected about 2,500 offers. At the end of the tendering process, each company that participated received feedback, with the aim of improving the process. A second tendering collected 637 offers. The interpolation between the CHF/kWp ratio and the total investment in CHF was then calculated for each company. Cross-sectional analysis shows that the average of R-square is closer to one in the second phase, which can be interpreted as a better consistency in the construction and in the pricing of the bids. The increase of minimum values shows that the companies furthest away from the theoretical model have made significant progress. Our study therefore shows that with proper support, the solar panel installation companies are more competitive and can help accelerate energy transition. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.